2010
DOI: 10.1177/0093854810363569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of South Carolina’s Sex Offender Registration and Notification Policy on Deterrence of Adult Sex Crimes

Abstract: This study examined whether South Carolina’s sex offender registration and notification (SORN) policy was associated with a general deterrent effect on adult sex crimes. Using adult arrest data from 1990 through 2005, trend analyses modeled the intervention effects of 1995 (the year South Carolina’s SORN policy was initially implemented) and 1999 (the year the policy was revised to include online registration). Results supported a significant deterrent effect for the 1995 intervention year, with an approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 24 publications
2
33
3
Order By: Relevance
“…These laws, referred to as Sexually Violent Predator (SVP) laws, include mandates such as sex offender registration (i.e., The Jacob Wetterling Act), community notification (i.e., Megan's Law), and residence restrictions (Levenson, 2003). Despite research suggesting these policies have little effect on sex offender recidivism (Letourneau, Levenson, Bandyopadhyay, Armstrong, & Sinha, 2010;Tewksbury & Jennings, 2010;Zandbergen, Levenson, & Hart, 2010), and may even exacerbate a released sex offender's ability to successfully reintegrate (Levenson, D'Amora, & Hern, 2007;Tewksbury, 2007), several researchers have discovered strong public support for them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These laws, referred to as Sexually Violent Predator (SVP) laws, include mandates such as sex offender registration (i.e., The Jacob Wetterling Act), community notification (i.e., Megan's Law), and residence restrictions (Levenson, 2003). Despite research suggesting these policies have little effect on sex offender recidivism (Letourneau, Levenson, Bandyopadhyay, Armstrong, & Sinha, 2010;Tewksbury & Jennings, 2010;Zandbergen, Levenson, & Hart, 2010), and may even exacerbate a released sex offender's ability to successfully reintegrate (Levenson, D'Amora, & Hern, 2007;Tewksbury, 2007), several researchers have discovered strong public support for them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Letourneau et al (2010) suggest that different states with varying policies may have differential effects. They also suggest that different research methods, sample groups, definitions of recidivism, and types of statistical analysis may affect results in each study.…”
Section: Registration and Notificationmentioning
confidence: 99%
“…They also suggest that different research methods, sample groups, definitions of recidivism, and types of statistical analysis may affect results in each study. Notably, Letourneau et al (2010) found that South Carolina's initial SORN policy had a general deterrent effect, with a nearly 11 percent reduction in the monthly rate of first time sex offense arrests. Practically, the researchers found that this number translates to three sex crime arrests being avoided each month post-policy.…”
Section: Registration and Notificationmentioning
confidence: 99%
“…However, it seems counter-intuitive that online notification would fail to enhance a general deterrent effect, given that this mechanism equates with public shaming of arrestees who themselves attribute serious consequences to public notification, including loss of employment, housing, friends and the support of family (Levenson and Cotter, 2005; Wikström, 2008). We argue that Letourneau et al (2010b) original study was limited in that the separate analysis of registration vs. notification implementation might not have captured a sequential (and progressive) effect of these interventions. Moreover, their analyses adhered to traditional Box-Jenkins intervention ARIMA models and did not consider investigating the relevancy (or redundancy) of the information content of the time-series inputs (past values of the series) to arrive at a desirable prediction/forecasting model (Lendasse et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In an evaluation of the general deterrent effect of SC’s SORN policy, Letourneau et al (2010b) conducted univariate Box-Jenkins interrupted auto-regressive integrated moving average (ARIMA) analysis (Box et al , 1994) to understand general deterrence of SC SORN policies on sex crime arrestees, separately for the initial implementation of registration in 1995 and the subsequent implementation of online notification in 1999. They reported a significant intervention effect for 1995, but not for 1999.…”
Section: Introductionmentioning
confidence: 99%